Vietnam and beyond : Tim O'Brien and the power of storytelling - Ciocia, Stefania (Liverpool University Press, 2012)
"Vietnam and Beyond: Tim O'Brien and the Power of Storytelling is a comprehensive, in-depth study of one of the most thought-provoking writers of the Vietnam war generation. This volume breaks away from previous readings of O'Brien's development as a trauma artist and an outspoken chronicler of the American involvement in Vietnam: its thematic, rather than chronological, approach contextualizes O'Brien's work beyond the confines of war literature. The necessary exploration of O'Brien's recurrent engagement with the conflict in Vietnam leads to a thorough discussion of the writer's revision of key American (and western) ideas and concerns: the association between courage, heroism and masculinity, the celebration of the pioneering spirit in the frontier narrative, the sense of superiority in the encounter with foreign civilizations, the fraught relationship between power and truth, or reality and imagination, and the attempt and the right to speak about unspeakable events. All these themes, as Ciocia illustrates, highlight O'Brien's compelling preoccupation with the role and the ethical responsibility of the storyteller. With his clear privileging of 'story-truth' over 'happening-truth', O'Brien makes a bold, serious investment in the power of fiction, as testified by his formal experimentations, metanarrative reflections and sustained meditations on matters such as individual agency, moral accountability and authenticity. Approached from this fresh perspective, O'Brien emerges as a figure deserving to find a wider audience and demanding renewed scholarly attention for his remarkable achievements as a contemporary mythographer, an acute observer of the human condition and a sharp critic of American culture."--Publisher's website.